2022
DOI: 10.1021/acsphotonics.2c00076
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Creation of the Room-Temperature Coherently Controllable ST1 Spin Center in Diamond

Abstract: Among hundreds of optically active solid-state defects, very few of them hold the promise of spin qubits coherently operating at room temperature. Besides the prominent nitrogen-vacancy (NV) center in diamond, the more recently discovered ST1 center possesses advantageous electronic and spin properties such as a spin-free ground state and a large spin readout contrast (>50%) at 300 K. However, because of its unknown nature, the ST1 center was never created on demand or computed theoretically. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…In a recent report, a systematic study has been carried out by implanting different ions into CVD diamond, and then the sample was imaged by scanning confocal microscope to monitor the presence of ST1 color center [15]. They found that the occurrence of ST1 color center is associated with the implanted oxygen ions, thus the defect should contain oxygen [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent report, a systematic study has been carried out by implanting different ions into CVD diamond, and then the sample was imaged by scanning confocal microscope to monitor the presence of ST1 color center [15]. They found that the occurrence of ST1 color center is associated with the implanted oxygen ions, thus the defect should contain oxygen [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, a systematic study has been carried out by implanting different ions into CVD diamond, and then the sample was imaged by scanning confocal microscope to monitor the presence of ST1 color center [15]. They found that the occurrence of ST1 color center is associated with the implanted oxygen ions, thus the defect should contain oxygen [15]. Because of the low yield of the ST1 center, it was speculated that the ST1 center should be a complex of oxygen and vacancy, and it might also contain another impurity such as hydrogen [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Color centers in diamond represent an emerging class of solid-state systems for single-photon emission, [1][2][3][4][5][6][7][8] with appealing applications in quantum-enhanced technologies, including quantum information processing and quantum sensing. [9][10][11][12][13][14][15][16][17][18] Among them, point-defects related to group-IV impurities have displayed promising properties in terms of high photon emission rate, relatively narrow spectral signatures, and spin-dependent emission properties.…”
Section: Introductionmentioning
confidence: 99%